PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN KECURANGAN PADA AUTO2000 DI KOTA BANDUNG - Krismayanti, Yanti (Universitas Logistik dan Bisnis Internasional, 2025)
Auto2000 is Established in 1975, the company operates in the domains of Toyota spare parts sales, maintenance, repairs, and supply. Auto2000 has several services including buying and selling vehicles, servicing vehicles, buying and selling spare parts, and repairing and painting vehicle bodies that are spread across almost throughout Indonesia. Before fraud occurs in a company or organization, supervision is formed in accordance with the internal control system in running a company or organization which of course will be carried out by professional experts in the field of internal control systems. With this internal control system, it is hoped that it will be able to prevent fraud in a company. This study aims to prove the research method, namely quantitative and this research uses the main data collected took the form of surveys through questionnaires, involving a total sample size of 42 and 38 respondents who filled out the questionnaire. The results of this study indicate that the internal control system for fraud prevention at Auto2000 in the city of Bandung has a strong variable. In this study it can be interpreted that the internal control system exerts a constructive and noteworthy impact on fraud prevention at Auto2000 in the city of Bandung.